Using several types of virtual characters in sports - a literature survey - Petri, K.; Bandow, N.; Witte, K. (International Journal of Computer Science in Sport, 2018)
This article discusses the development and application of virtual environments (VEs) in the domain of exercise as well as research in recreational and high-performance sports. A special focus is put on the use of virtual characters (VCs). For its elaboration, the following criteria parameters were chosen: scene content and the role of the VC, output device, kind of additional feedback, level of expertise of the tested participants, kind of user`s movement (reaction), kind of the visualization of the user`s body, kind of study and kind of evaluation. We explored the role of VCs embodying virtual opponents, teammates, or coaches in sports. We divided these VCs in passive and autonomous characters. Passive VCs are not affected by the user, whereas autonomous VCs adapt autonomously to the user`s movements and positions. We identified 44 sport related VEs, thereof 22 each in the domain of recreational sports and high-performance sports: of the identified 44 VEs, 19 VEs are without VC, 20 VEs with passive VCs, and 5 VEs with autonomous VCs. We categorized studies examining expert athletes in high-performance sports as well as studies analyzing novices, beginners or advanced athletes in recreational sports. Nevertheless, all identified systems are suitable for athletes of recreational and high-performance level.